Applied Statistics Manual : A Guide to Improving and Sustaining Quality with Minitab. - Smith, Joel (Quality Press, 2018)
This book was written to provide guidance for those who need to apply statistical methods for practical use. While the book provides detailed guidance on the use of Minitab for calculation, simply entering data into a software program is not sufficient to reliably gain knowledge from data. The software will provide an answer, but the answer may be wrong if the sample was not taken properly, the data was unsuitable for the statistical test that was performed, or the wrong test was selected. It is also possible that the answer will be correct, but misinterpreted. This book provides both guidance in applying the statistical methods described as well as instructions for performing calculations without a statistical software program such as Minitab. One of the authors is a professional statistician who spent nearly 13 years working at Minitab and the other is an experienced and certified Lean Six Sigma Master Black Belt. Together, they strive to present the knowledge of a statistician in a format that can be easily understood and applied by non-statisticians facing real-world problems. Their guidance is provided with the goal of making data analysis accessible and practical. Rather than focusing on theoretical concepts, the book delivers only the information that is critical to success for the practitioner. It is a thorough guide for those who have not yet been exposed to the value of statistics, as well as a reliable reference for those who have been introduced to statistics but are not yet confident in their abilities. Supplemental files available! If you are an instructor who would like to conduct training with this book, please visit this "https://asqassets.widencollective.com/portals/sybdffda/(H1550)AppliedStatisticsManualAGuidetoImprovingandSustainingQualitywithMinitab" access: Course descriptions for one or two semester university courses Chapter descriptions for standalone sessions A data file containing data sets used in the book